Pelatihan Perancangan Dan Implementasi Database Untuk Meningkatkan Kompetensi Siswa SMK di LKP Pelita Media - Guntur Maha Putra; Ahmad Muhazir; Jumiah (Jurdimas (Jurnal Pengabdian Kepada Masyarakat) Royal, 2026)
Abstract: The training on database design and implementation for vocational high school students at LKP Pelita Media aims to enhance students’ understanding of fundamental database concepts as well as their ability to design and implement databases through a library application case study. The main problem addressed is the limited competence of students in structured database design, including data requirement analysis, Entity Relationship Diagram (ERD) development, normalization, and the lack of practical experience in using MySQL and applying it to real-world cases. The method employed consists of integrated theory- and practice-based training through interactive lectures, demonstrations, hands-on practice, and mentoring. The activities were conducted in four stages: introduction to database concepts, ERD design and normalization, SQL implementation (CRUD and JOIN), and integration with a simple web application. The results indicate that participants gained improved understanding and skills in designing and implementing databases, aligned with current developments in information technology, particularly in the context of a library application case study. Keywords: database; ERD; MySQL; normalization; training Abstrak: Pelatihan perancangan dan implementasi database bagi siswa SMK di LKP Pelita Media bertujuan meningkatkan pemahaman konsep dasar basis data serta kemampuan merancang dan mengimplementasikan database pada studi kasus aplikasi perpustakaan. Permasalahan utama adalah terbatasnya kompetensi siswa dalam perancangan database secara terstruktur, meliputi analisis kebutuhan data, pembuatan Entity Relationship Diagram (ERD), normalisasi, serta kurangnya pengalaman praktik menggunakan MySQL hingga implementasi pada kasus nyata. Metode yang digunakan berupa pelatihan berbasis teori dan praktik terintegrasi melalui ceramah interaktif, demonstrasi, praktik langsung, dan pendampingan. Kegiatan dilaksanakan dalam empat tahap, yaitu pengenalan konsep basis data, perancangan ERD dan normalisasi, implementasi SQL (CRUD dan JOIN), serta integrasi dengan aplikasi web sederhana. Hasil menunjukkan peserta memiliki pemahaman dan keterampilan perancangan serta implementasi database yang relevan dengan perkembangan teknologi informasi khususnya pada studi kasus aplikasi perpustakaan. Kata kunci: database; ERD; MySQL; normalisasi; pelatihan